The inscription in the Hellenistic mosaic of Ilici (La Alcudia, Elche) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The mosaic inscription from La Alcudia, the ancient Iberian city of Ilici, is excepcional because it is the most ancient opus tessellatum inscription discovered in Hispania and also because it is one of the few inscriptions that could be classified as an Iberian text written in Latin alphabet. The aim of this paper is to propose a new lecture according to the autopsy and make some remarks on its interpretation according to the Latin parallels.
Keywords: Iberian personal names; Iberian language; Latin alphabet; Mosaic inscription; Latinization